2016
DOI: 10.3102/0013189x16671718
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Minority Teachers

Abstract: The demographic divide between teachers and students is of growing public concern. However, few studies have explicitly addressed the common argument that students, and particularly minority students, have more favorable perceptions of minority versus White teachers. Using data from the Measure of Effective Teaching study, we find that students perceive minority teachers more favorably than White teachers. There is mixed evidence that race matching is linked with more favorable student perceptions. These findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(63 citation statements)
references
References 40 publications
2
61
0
Order By: Relevance
“…Research supports this sentiment, with one recent study linking racial minority teachers to more favorable perceptions from students of all races. 10…”
Section: Strengthsmentioning
confidence: 99%
See 3 more Smart Citations
“…Research supports this sentiment, with one recent study linking racial minority teachers to more favorable perceptions from students of all races. 10…”
Section: Strengthsmentioning
confidence: 99%
“…In addition, many of the above mentioned social psychological interventions have strong research evidence of effectiveness and are relatively easy to implement. 10 There are a number of strategies to integrate a social psychological intervention into District practices. During the task force meeting, members primarily discussed an approach that consisted of giving out writing tasks to students in the classrooms.…”
Section: Recommendation 8: Social Psychological Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Countless research has established to date that such stereotypes about race have permeated education in harmful waves, and pushed individuals, who vowed to educate the masses, to close off opportunities of education to underrepresented groups even by their grading attitudes, expectations, and behaviors in class. Researchers analyzed educational, demographic, and survey data of 10,000 high school sophomores and their teachers using the Education Longitudinal Study of 2002, to show that teachers typically underestimating their students' abilities, actually created a negative impact on their academic expectations of themselves, and this was especially harmful among Black students (Cherng and Halpin, 2016;Cherng, 2017). Further, Fleming (1984), and Smedley et al (1993) along with a large body of recent research (Locks et al, 2008;Hurtado et al, 2009) demonstrated that racial biases encountered in school severely negatively impacted Black students' academics, critical thinking, sense of belonging, and emotional development through heightened stress levels.…”
Section: Crogmanmentioning
confidence: 99%